2018
DOI: 10.4049/jimmunol.1800322
|View full text |Cite
|
Sign up to set email alerts
|

Conventional Dendritic Cells Impair Recovery after Myocardial Infarction

Abstract: Ischemic myocardial injury results in sterile cardiac inflammation that leads to tissue repair, two processes controlled by mononuclear phagocytes. Despite global burden of cardiovascular diseases, we do not understand the functional contribution to pathogenesis of specific cardiac mononuclear phagocyte lineages, in particular dendritic cells. To address this limitation, we used detailed lineage tracing and genetic studies to identify bona fide murine and human CD103 conventional dendritic cell (cDC)1s, CD11b … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(48 citation statements)
references
References 78 publications
3
42
0
Order By: Relevance
“…With CD11c + cell depletion, 24 weeks after TAC, mice exhibit reduced LV fibrosis and decreased expression of fibroblast activating genes (Wang et al, 2017). These studies are met with similar critiques regarding lack of DC specificity, however, studies using a more specific model of cDC ablation also show decreased LV fibrosis 3 weeks post-MI (Lee et al, 2018). These findings are further supported by earlier studies which show cardiac and splenic DC activation and expansion 8 weeks post-MI (Ismahil et al, 2014).…”
Section: Dendritic Cellssupporting
confidence: 53%
“…With CD11c + cell depletion, 24 weeks after TAC, mice exhibit reduced LV fibrosis and decreased expression of fibroblast activating genes (Wang et al, 2017). These studies are met with similar critiques regarding lack of DC specificity, however, studies using a more specific model of cDC ablation also show decreased LV fibrosis 3 weeks post-MI (Lee et al, 2018). These findings are further supported by earlier studies which show cardiac and splenic DC activation and expansion 8 weeks post-MI (Ismahil et al, 2014).…”
Section: Dendritic Cellssupporting
confidence: 53%
“…In line with these findings, the CD103 + DCs subset in the aortic wall expanded in response to Flt-3L injection, and was absent in mice deficient in Flt-3, indicating that the development of the CD103 + DCs requires Flt-3/Flt-3L interaction, and they are derived from classical Flt3L-dependent pre-DC precursors (18). Recently, a lineage tracing study revealed that the CD103 + DCs in the cardiovascular tissues could be developed from an intermediate CD103 − CD11b − DC subset that expressed IRF8 and expanded readily in response to Flt-3L administration (34).…”
Section: Cd103 + Dcs In Atherosclerosismentioning
confidence: 99%
“…Epididymal AT was harvested and minced into small pieces. Single cells were isolated by enzymatic digestion for 20 min at 37 • C with gentle shaking using a collagenase mixture containing collagenase I, collagenase XI, and hyaluronidase (Sigma) in Hanks balanced salt solution containing Ca + /Mg + and 5% FBS (Wisent), as described (27). After digestion, the single cells and remaining tissue were passed through a 70-µm cell strainer.…”
Section: Single-cell Preparation For Flow Cytometrymentioning
confidence: 99%